(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2018)
The paper aims to continue a dialogue with Stefano Rodotà on the role and desirable features of Law, and in particular of Private Law, with regard to the open issues in Bioethics. The main legacy of Stefano Rodotà is assessed with special regard to: a) the need for a “Constitutional Civil Law”, viewed in a unitary system centered on the Person; b) the need for a continuous tension between life and rules, which imposes a constant concretization of a “new habeas corpus”, based on the indivisibility of the principles of freedom, equality and solidarity, revisited in the light of dignity; c) the characteristics and consequences of a “flexible” and “demanding” Law. The recent Law n. 219/2017 on informed consent and advance directives is evaluated in this perspective.